OVERVIEW OF XUNIT FRAMEWORK CUSTOMIZATION CAPABILITIES FOR UNIT TESTING .NET APPLICATIONS - YEVSEIENKO, OLEH; ZUEV, ANDREY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article is devoted to exploring the effectiveness of using the xUnit framework for unit testing software solutions on the .NET platform. The relevance of the topic is driven by the increasing need for high-quality code coverage in the context of rapid development of web and desktop applications, as well as the widespread adoption of component-oriented architectures, particularly Blazor. A comparative analysis of xUnit with other popular frameworks such as NUnit and MSTest is presented, taking into account criteria such as ease of use, performance, extensibility, and compatibility with CI/CD pipelines. Typical use cases of xUnit are described for projects of varying scales, including API testing, business logic validation, and user interface component testing. The findings indicate that xUnit offers high flexibility and broad integration with modern development tools. At the same time, some features — such as test retries or integration with external data sources — are not available by default and require third-party extensions or additional configuration. The literature review confirms that automated testing is a key element in ensuring software quality and a necessary step in the development of complex software systems with a high number of dependencies. In the practical section, approaches to extending xUnit functionality are proposed, including the use of custom attributes and custom test categorization mechanisms. Particular attention is paid to the implementation of test categorization infrastructure using the Trait attribute and the options for filtering tests in Visual Studio and through the command-line interface (CLI). The article may be useful for both novice and experienced developers seeking to optimize the unit testing process in the .NET environment.
Keywords: unit test; automated testing; framework; xUnit; programming; software tools